IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 TENTANG PENGELOLAAN KEUANGAN DESA DI DESA SEMUNAI KECAMATAN PINGGIR KABUPATEN BENGKALIS PROVINSI RIAU - Markus Lato Munthe; Junaidi Junaidi; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Villages are customary villages and villages or what are referred to by other names arelegal community units that have territorial boundaries that are authorized to regulate andmanage government affairs, local community interests based on community initiatives, originrights, and/or traditional rights that are recognized and respected in system of government ofthe Unitary State of the Republic of Indonesia, Village Financial Management is the wholeactivity which includes planning, implementation, administration, reporting, andaccountability of Village finances. Whereas Village finance means that all Village rights andobligations can be valued in money and everything in the form of money and goods related tothe implementation of Village rights and obligations. In writing this thesis, the author tries toimplement Article 2 of the Minister of Home Affairs Regulation Number 20 of 2018 concerningVillage Financial Management in Semunai Village, Pinggir District, Bengkalis Regency, RiauProvince.The objectives of writing this thesis are: first, to find out the implementation of Article2 of the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village FinancialManagement in Semunai Village, Pinggir District, Bengkalis Regency, Riau Province. Second,to find out the inhibiting factors in the implementation of Article 2 of the Minister of HomeAffairs Regulation Number 20 of 2018 concerning Village Financial Management in SemunaiVillage, Pinggir District, Bengkalis Regency, Riau Province. The research method in this thesisuses a type of sociological legal research, namely research on the effectiveness of laws thatlive in society. The nature of this thesis research is research descriptive which describessystematically, the facts and characteristics of the object studied appropriately. The datasource used is the data source first, seconds and tertiary The data collection techniques in thisstudy were interviews, questionnaires and literature review. After the data was collected, itwas analysed to draw conclusions.Based on the results of the research, the first conclusion can be drawn that theimplementation of the principles of village financial management in Semunai Village, seenfrom the principles of transparency, accountability, participation, as well as orderly anddisciplined budgets, is quite good. participatory in Semunai village, organizers and theSemunai village community understand enough about the principles of village financialmanagement community, and other factors, namely the existence of misunderstandingsbetween the community and the village government regarding the implementation of villageactivities and the provision of village financial information.Keywords: Village, Management, Village Finance